Intra‐Articular Biomechanical Changes of the Meniscus and Ligaments During Stance Phase of Gait Circle after Different Anterior Cruciate Ligament Reconstruction Surgical Procedures: A Finite Element Analysis - Zi‐mu Mao; Zhen‐wei Wang; Chao Xu; Chen‐he Liu; Zhi‐yu Zhang; Xiao‐li Ren; An‐qi Xue; Ze‐nan Li; Feng Zhao; Qi Yao; Jia‐kuo Yu (Orthopaedic Surgery, 2022)
Objective The debate on the superiority of single‐ or double‐bundle for anterior cruciate ligament reconstruction has not ceased. The comparative studies on intra‐articular biomechanics after different surgical reconstructions are rare. This study is to evaluate the biomechanical stress distribution intra‐knee after single‐ and double‐bundle anterior cruciate ligament reconstruction by three‐dimensional finite element analysis, and to observe the change of stress concentration under the condition of vertical gradient loads. Methods In this study, magnetic resonance imaging data were extracted from patients and healthy controls for biomechanical analysis. Patients included in the three models were matched in age and sex. The strength and distribution of induced stresses were analyzed in two frequently used procedures, anatomical single‐bundle anterior cruciate ligament reconstruction and anatomical double‐bundle anterior cruciate ligament reconstruction, using femoral‐graft‐tibial system under different loads, to mimic a post‐operation mechanical motion. The three‐dimensional finite‐element models for normal ligament and two surgical methods were applied. A vertical force simulating daily walking was performed on the models to assess the interfacial stresses and displacements of intra‐articular tissues and ligaments. The evaluation results mainly included the stress of each part of ligament and meniscus. The stress values of different parts of three models were extracted and compared. Results The stress of ligament/graft at femoral side of three finite‐element models was significantly higher than at tibial side, while the highest level was observed in single‐bundle reconstruction finite‐element model. With the increase of force, the maximum stress in the medial (7.1–7.1 MPa) and lateral (4.9–7.4 MPa) meniscus of single‐bundle reconstruction finite‐element model shifted from the anterior horn to the central area (p = 0.0161, 0.0479, respectively). The stress was shown to be at a lower level at femoral side and posterior cruciate ligament of intra‐knee in two reconstruction finite‐element models than that in normal finite‐element models, while presented higher level at the tibial side than normal knee (p = 0.3528). The displacement of the femoral side and intra‐knee areas in reconstruction finite‐element models was greater than that in normal finite‐element model (p = 0.0855). Conclusion Compared with the single‐bundle technique, the graft of double‐bundle anterior cruciate ligament reconstruction has better stress dissipation effect and can prevent postoperative meniscus tear more effectively.